1, 3‐Dehydro‐o‐Carborane: Generation and Reaction with Arenes1. Issue 32 (1st July 2014) - Zhao, Da; Zhang, Jiji; Xie, Zuowei
Abstract Like the importance of benzyne, witnessed in modern arene chemistry for decades, 1, 2‐dehydro‐o‐carborane (o‐carboryne), a three‐dimensional relative of benzyne, has been used as a synthon for generating a wide range of cage, carbon‐functionalized carboranes over the past 20 years. However, the selective B functionalization of the cage still represents a challenging task. Disclosed herein is the first example of 1, 3‐dehydro‐o‐carborane featuring a cage CB bond having multiple bonding characters, and is successfully generated by treatment of 3‐diazonium‐o‐carborane tetrafluoroborate with non‐nucleophilic bases. This presents a new methodology for simultaneous functionalization of both cage carbon and boron vertices.